Real-time PCR using mycobacteriophage DNA for rapid phenotypic drug susceptibility results for Mycobacterium tuberculosis - Suporn Pholwat (2018)
Managing drug-resistant Mycobacterium tuberculosis requires drug susceptibility testing, yet conventional drug susceptibility testing is slow, and molecular testing does not yield results for all antituberculous drugs. We addressed these challenges by utilizing real-time PCR of mycobacteriophage D29 DNA to evaluate the drug resistance of clinical M. tuberculosis isolates. Mycobacteriophages infect and replicate in viable bacterial cells faster than bacterial cells replicate and have been used for detection and drug resistance testing for M. tuberculosis either by using reporter cells or phages with engineered reporter constructs. Our primary protocol involved culturing M. tuberculosis isolates for 48 h with and without drugs at critical concentrations, followed by incubation with 10 3 PFU/ml of D29 mycobacteriophage for 24 h and then real-time PCR. Many drugs could be incubated instantly with M. tuberculosis and phage for 24 h alone. The change in phage DNA real-time PCR cycle threshold (C T ) between control M. tuberculosis and M. tuberculosis treated with drugs was calculated and correlated with conventional agar proportion drug susceptibility results. Specifically, 9 susceptible clinical isolates, 22 multidrug-resistant (MDR), and 1 extensively drug-resistant (XDR) M. tuberculosis strains were used and C T control-C T drug cutoffs of between +0.3 and -6.0 yielded 422/429 (98%) accurate results for isoniazid, rifampin, streptomycin, ethambutol, amikacin, kanamycin, capreomycin, ofloxacin, moxi- floxacin, ethionamide, para-aminosalicylic acid, cycloserine, and linezolid. Moreover, the ΔC T values correlated with isolate MIC for most agents. This D29 quantitative PCR assay offers a rapid, accurate, 1- to 3-day phenotypic drug susceptibility test for first- and second-line drugs and may suggest an approximate MIC. Copyright © 2012, American Society for Microbiology. All Rights Reserved.